Coucou c'est important et j'ai besoin d'aide au plus vite !

Factorise les expressions suivantes:

A= (x+1)² - 36

B= 25-(2x+3)²

C= 49x² - 16

D= 9y² - 24y + 16

E= x² + 2x +1

F= 25 - 100t²

G= 36z² - 1

H= 64-80x+ 25x²

1

Réponses

2014-02-08T11:28:16+01:00
A= (x+1)² - 36 = (x+1+6)(x+1-6) = (x+7)(x-5)

B= 25-(2x+3)² = (5+2x+3)(5-2x-3) = (2x+8)(-2x+2)

C= 49x² - 16 = (7x+4)(7x-4)

D= 9y² - 24y + 16 = (3y-4)²

E= x² + 2x +1 delta=0 -> (x+1)²

F= 25 - 100t² = (5+10t)(5-10t)
G= 36z² - 1 = (6z+1)(6z-1)

H= 64-80x+ 25x² = (5x-8)²